2008
DOI: 10.1038/nature07182
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 controls a brown fat/skeletal muscle switch

Abstract: Summary Brown fat can increase energy expenditure and protect against obesity through a specialized program of uncoupled respiration. We show here by in vivo fate mapping that brown but not white fat cells arise from precursors that express myf5, a gene previously thought to be expressed only in the myogenic lineage. Notably, the transcriptional regulator, PRDM16 controls a bidirectional cell fate switch between skeletal myoblasts and brown fat cells. Loss of PRDM16 from brown fat precursors causes a loss of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

70
2,072
5
31

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,087 publications
(2,222 citation statements)
references
References 43 publications
70
2,072
5
31
Order By: Relevance
“…Previous studies claimed that MPs are able to differentiate into white46, 47, 48 or brown‐like adipocytes26, 27 under certain conditions. However, most of these studies relied on single muscle fibre isolations46, 47, 48 or on pre‐plating of collagenase‐digested tissue47 to obtain the progenitor populations, which could potentially result in the isolation of non‐myogenic, interstitial cells surrounding myofibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies claimed that MPs are able to differentiate into white46, 47, 48 or brown‐like adipocytes26, 27 under certain conditions. However, most of these studies relied on single muscle fibre isolations46, 47, 48 or on pre‐plating of collagenase‐digested tissue47 to obtain the progenitor populations, which could potentially result in the isolation of non‐myogenic, interstitial cells surrounding myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…Seale et al 26. have shown that primary myoblasts isolated from newborn mice are able to differentiate into brown adipocytes when expression of the transcription factor PRDM16 is induced.…”
Section: Introductionmentioning
confidence: 99%
“…Again it should not be surprising that acquirement of thermogenic competence is not paralleled by promotion of adipose conversion, as the brown adipocytes studied here are of a different lineage from those giving rise to white adipocytes and are more related to muscle cells. 19,20,44,45 …”
Section: Discussionmentioning
confidence: 99%
“…However, in the early phases of differentiation, brown adipocytes express a series of myogenic genes, both transcription factors and structural proteins, 19 and the lineage of classical brown adipocytes is closely related to that of skeletal muscle. 20 Thus, acquisition of an adipocyte phenotype may not indicate progression to fully differentiated brown adipocyte characteristics. As the myogenic gene expression is transient during brown adipocyte development, myogenic genes cannot be chosen as differentiation markers.…”
Section: Introductionmentioning
confidence: 99%
“…It is not yet clear whether intermuscular AT from appearance onwards expresses the cellular and molecular features of primarily brown AT or of both brown and white AT. This question is reinforced by the recent characterization in mice of two distinct adipose cell precursors: one committed in either brown adipocytes or muscular cells, and the second is committed in either brown or white adipocyte (Seale et al, 2008). These recent findings could prompt the hypothesis that intermuscular AT, due to its muscle-based anatomical location, has a cellular origin similar to that of muscle, consequently leading to different cellular and metabolic features to those reported for perirenal AT during foetal life.…”
Section: Introductionmentioning
confidence: 99%